Motivation for patient engagement in patient safety: a multi-perspective, explorative survey - Caroline Raab; Nikoloz Gambashidze; Larissa Brust; Matthias Weigl; Amelie Koch (BMC, 2024)
Abstract Background and Objectives Despite increasing calls for more patient engagement in patient safety, limited knowledge remains on what actually motivates key stakeholders in healthcare to promote patient engagement. We therefore set out to survey key stakeholders of patient engagement in patient safety (i.e., patients, healthcare professionals, and managers). We aimed to identify and explore stakeholder's distinct and shared motives for patient engagement. Methods A stepwise Delphi method was applied, utilizing semi-structured online interviews for determination of stakeholder motives for patient engagement in patient safety. In a subsequent online survey, statements were evaluated and identified. 34 subject-matter experts from all relevant stakeholder groups completed the online interviews and 33 the online survey. We used content analysis approaches for qualitative and descriptive analyses for quantitative measures. Further, we evaluated the consensus on distinct and shared motives across stakeholder groups. Results Seven key motives for patient engagement in patient safety were identified. Major motives attributed to patients were: (1) To improve experiences and care outcomes for oneself, as well as (2) for future patients, (3) to express gratitude and appreciation, (4) to cope successfully with treatment-related emotions. A motive shared by patients and professionals was (5) to contribute actively to improved delivery of healthcare. To optimize patient safety, costs, and care processes (6) was shared by professionals and managers. Lastly, (7) to improve patient-provider relationships was jointly shared by all stakeholder groups. For four motives (1, 2, 6, 7) consensus was established. Conclusions In order to unlock the full potential of future interventions in patient engagement, a deeper understanding of stakeholder motives is essential. We identified a set of distinct and shared motives for patient engagement across relevant stakeholder groups. Our findings may inform future interventions in patient engagement that take account of the motivational foundations and aspirations of all stakeholders who are key for the success for collaborative patient safety and care improvements. Trial registration ID DRKS00031837 (Date May 8, 2023).